2018
DOI: 10.1038/s41435-018-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated T cell levels in peripheral blood predict poor clinical response following rituximab treatment in new-onset type 1 diabetes

Abstract: Biologic treatment of type 1 diabetes (T1D) with agents including anti-CD3 (otelixizumab and teplizumab), anti-CD20 (rituximab), LFA3Ig (alafacept), and CTLA4Ig (abatacept) results in transient stabilization of insulin C-peptide, a surrogate for endogenous insulin secretion. With the goal of inducing more robust immune tolerance, we used systems biology approaches to elucidate mechanisms associated with C-peptide stabilization in clinical trial blood samples from new-onset T1D subjects treated with the B cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 42 publications
4
51
3
1
Order By: Relevance
“…We validated these findings with CBC and flow cytometry data and showed that they can be used to predict differential benefits of immunomodulatory therapy. In combination with other recent work on response to immunotherapy (9)(10)(11)(39)(40)(41), these results point toward precision targeting and modulation of therapy to achieve optimal benefits.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…We validated these findings with CBC and flow cytometry data and showed that they can be used to predict differential benefits of immunomodulatory therapy. In combination with other recent work on response to immunotherapy (9)(10)(11)(39)(40)(41), these results point toward precision targeting and modulation of therapy to achieve optimal benefits.…”
Section: Discussionmentioning
confidence: 75%
“…In order to interrogate immunological differences with rate of T1D progression in an unbiased manner, we used whole blood gene expression profiling by RNA-seq (see Methods). We have previously used this approach to investigate response to treatment in new-onset T1D, including variation in rates of C-peptide loss following immunotherapy (9)(10)(11). We performed RNA-seq analysis on all subjects for whom sufficient samples were available; included subjects did not differ from total study populations in age at T1D diagnosis, sex, baseline C-peptide, baseline HbA1c, or rate of C-peptide change ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as in all immune therapy, there is a range of responses among those treated with active drug. Poor responders to the B cell depletion therapy rituximab were found to have an increase in activated T cell gene transcripts , and those who had poor responses to abatacept had an increase in B cell gene transcripts . Whether or not these transcriptional changes were due to changes in proliferation could be addressed in subsequent clinical trials, with therapies expected to impact T cell turnover using the short heavy glucose labeling protocol described here.…”
Section: Discussionmentioning
confidence: 98%